Social Media's Role as a Marketing Medium for SME Products - Bunga Aditi; Kalvin Sinaga; Muller Tamba; Olga Theolina Sitorus; Sopi Pentana (Pusat Riset dan Inovasi Nasional, 2023)
Engagement dedication SMEs for processed goods such as craft bamboo, chips banana, jam tomato, cranky corn, and so on are employed by the residents of Village Sandpaper Subdistrict Sandpaper Field City Medan, North Sumatra, where this is being done. The purpose of this activity is to teach locals how to use social media platforms like Instagram and WhatsApp to market their products. Sales of locally produced goods are expected to increase market share, boost efficiency in marketing, and use other strategies to make the most of already-existing social media platforms that are controlled by residents. These strategies should also improve the quality of goods that are more productive, rather than just sending messages.